Measurements and Monte Carlo simulations of high-energy neutron streaming through the access maze using activation detectors at 24 GeV/c proton beam facility of CERN/CHARM. Issue 8 (3rd August 2021) - Nakao, Noriaki; Kajimoto, Tsuyoshi; Sanami, Toshiya; Froeschl, Robert; Iliopoulou, Elpida; Infantino, Angelo; Yashima, Hiroshi; Oyama, Takahiro; Nagaguro, Seiji; Lee, Eunji; Matsumoto, Tetsuro; Masuda, Akihiko; et al.
ABSTRACT: A measurement of high-energy neutron streaming was performed through a maze at the CERN (Conseil Européen pour la Recherche Nucléaire) High-energy AcceleRator Mixed-field (CHARM) facility. The protons of 24 GeV/c were injected onto a 50-cm-thick copper target and the released neutrons were streamed through a maze with several corridor-legs horizontally designed with the shield walls in the facility. Streaming neutrons were measured by using aluminum activation detectors placed at 10 locations in the maze. From the radionuclide production rate in the activation detectors, the attenuation profile along the maze was obtained for the reaction of 27 Al(n, α) 24 Na. Monte Carlo simulations performed with two codes, the Particle and Heavy Ion Transport System (PHITS) and CERN FLUktuierende KAskade (FLUKA), gave good agreements with the measurements within a factor of 1.7 for the production rates ranging over more than 3 orders of magnitude.